Monitoring System for Portable Mini Wind Energy with DC Water Pump Application - Shahriman, Wan Muhammad Haekal; Jumaat, Siti Amely (Journal of Electronic Voltage and Application, 2022)
Nowadays, renewable energy is becoming the most reliable way to generate electricity in exchange with non-renewable energy which commonly comes from coals and gases. This project is about the monitoring system of mini wind energy with DC water pump application harvested from seaside area. Thus, the project addresses the development of prototype of mini wind energy with monitoring system by using Arduino UNO as main microcontroller. For the project development, the voltage and current sensors are used to monitor the mini wind energy system’s performance. The NodeMCU ESP8266 board was used to allow communication between system and device through the Blynk application. Blynk is a platform used to include the Internet of Things (IoT) for this project. A mini wind energy data collection was conducted to assess the wind energy performance through manually reading the data from the LCD of the monitoring system and also through the Blynk application. The project was done at Pantai Punggor, Batu Pahat, Johor. The project was conducted to observe the capability of Mini Wind Energy to supply power to the 12V DC water pump as well as the monitoring system of the prototype. Based on the result, the load is observed to be working in a voltage of 13.22V, current at 0.19A and a power output of 2.51W with the average wind speed of 5.8 m/s.